1983
DOI: 10.1159/000299290
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent Cells in Uterine Cervical Lesions of Human Papillomavirus Origin

Abstract: To elucidate the local immunological reactions operative in the human papillomavirus (HPV)-induced lesions of the uterine cervix, a total of 150 cervical biopsies containing a dysplastic or a neoplastic change with (CO, 97 cases) or without (NCO, 53 cases) a coexistent HPV lesion (a flat, an inverted or a papillomatous condyloma) were subjected to ANAE (acid Α-naphthyl acetate esterase) staining of the immunocompetent cells; B and T lymphocytes, mononuclear phagocytes (MPS cells). In addition, HPV antigens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In the early 1980s, these studies were extended to cervical HPV lesions using newly introduced monoclonal antibodies to enumerate the cell subsets within these tissue-infiltrating lymphocytes (TIL) [29,30]. Different subsets of lymphocytes (B cells, T helper cells; T suppressor cells) were present in abundance among these TILs, located subjacent to but also within the HPV lesions, CIN and CC [29,30]. In addition, other types of immunocompetent cells, including Langerhans cells and natural killer cells were also detected among these infiltrates [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 1980s, these studies were extended to cervical HPV lesions using newly introduced monoclonal antibodies to enumerate the cell subsets within these tissue-infiltrating lymphocytes (TIL) [29,30]. Different subsets of lymphocytes (B cells, T helper cells; T suppressor cells) were present in abundance among these TILs, located subjacent to but also within the HPV lesions, CIN and CC [29,30]. In addition, other types of immunocompetent cells, including Langerhans cells and natural killer cells were also detected among these infiltrates [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Like studies enumerating immunocompetent cells among TILs in the baseline biopsies [29][30][31][32][33][34], also the present study suffers from the failure to provide any longitudinal data from the biopsies taken at FU visits [23,27]. It is to be emphasized that like the traffic (recirculation) of immunocompetent cells in the cervix, also the production of immune regulatory cytokines (like IL-10) is a highly dynamic process [14,15], being balanced and counterbalanced by a multitude of local and systemic stimuli that are impossible to record in single biopsies without a longitudinal setting.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that women with HIV infection have an increased risk of lower genital tract neoplasia [11][12][13][14], including cer vical, vaginal and vulvar intraepithelial neoplasia, with a prevalence from 22 to 70%. Both humoral and cellmediated immunity against the different types of HPV lesions has been disclosed [26], and, according to current understanding, the impairment of cell-mediated immuni ty seems to be the main factor predisposing to the devel opment and persistence of HPV infection and related cer vical dysplasia. An investigation of T lymphocyte subsets in women with manifested genital HPV infection showed a lower percentage of CD4+ cells (helper/inducer) and a higher percentage of CD8+ cells (cytotoxic/suppressor) compared with women with normal cervical cytologic evaluation [21].…”
Section: Discussionmentioning
confidence: 99%
“…They have been observed to vary considerably in number and distribution in genital warts, prompting speculation that this variability may reflect differences in host response to HPV-related lesions (81). Cellular infiltrates in the vicinity of cervical HPVrelated precursor lesions contain both B and T cells, although there is no clear explanation as to the significance of their presence (11,120). General studies of humoral immunity to papillomaviruses point to three humoral responses, including antibodies to HPV-derived proteins, the infected cells themselves, and antigens not directly associated with warts.…”
Section: Immunology Of Hpv General Studies Of Host Responsementioning
confidence: 99%
“…Immunohistochemical location of these proteins has not been demonstrated convincingly, leaving unclear their precise distribution and conditions under which they are expressed. RNA transcripts corresponding to these proteins have been identified in both cancer precursors and invasive cancers, suggesting that their expression is not limited to cells undergoing viral replication (20,120). Thus, it is likely that these proteins are produced even under circumstances in which viral integration has silenced expression of the other proteins (111).…”
Section: Characterization Of the Immune Response To Genital Hpvsmentioning
confidence: 99%